Early Experience of Helical Tomotherapy for Hepatobiliary Radiotherapy - Carole Massabeau; Virginie Marchand; Sofia Zefkili; Vincent Servois; François Campana; Philippe Giraud (Case Reports in Hepatology)
Helical tomotherapy (HT), an image-guided, intensity-modulated, radiation therapy technique, allows for precise targeting while sparing normal tissues. We retrospectively assessed the feasibility and tolerance of the hepatobiliary HT in 9 patients. A total dose of 54 to 60 Gy was prescribed (1.8 or 2 Gy per fraction) with concurrent capecitabine for 7 patients. There were 1 hepatocarcinoma, 3 cholangiocarcinoma, 4 liver metastatic patients, and 1 pancreatic adenocarcinoma. All but one patient received previous therapies (chemotherapy, liver radiofrequency, and/or surgery). The median doses delivered to the normal liver and to the right kidney were 15.7 Gy and 4.4 Gy, respectively, below the recommended limits for all patients. Most of the treatment-related adverse events were transient and mild in severity. With a median followup of 12 months, no significant late toxicity was noted. Our results suggested that HT could be safely incorporated into the multidisciplinary treatment of hepatobiliary or pancreatic malignant disease.